Reliable and sensitive physical testing of elite trapeze sailors - Bay, J.; Bojsen-Møller, J.; Nordsborg, N. B. (Scandinavian Journal of Medicine & Science in Sports, 2018)
It was investigated whether a newly developed discipline-specific test for elite-level trapeze sailors is reliable and sensitive. Furthermore, the physical demands of trapeze sailing were examined. In part 1, 9 national team athletes were accustomed to a simulated sailing test, which subsequently was completed on 4 occasions to determine test reliability and sensitivity to manipulations in body weight. Rope-pulling mean power output (MPO), oxygen consumption (VO2), heart rate (HR), and blood lactate values were acquired in all trials. In part 2, 6 sailors completed on-water racing with concurrent measurements of VO2, HR, and blood lactate. VO2max was determined during an incremental treadmill running test. Typical error, minimal difference, and ICC for average MPO in the test were 1.3%, 1.7%, and 0.99%, respectively. Adding 4 kg of external body weight caused a decrease in average MPO (270 ± 45W vs 265 ± 45W, P < .05) and an increase in VO2 (2.44 ± 0.23 L·min-1 vs 2.55 ± 0.26 L·min-1, P < .01). VO2, HR, and blood lactate during on-water sailing were 54.5% ± 7.2% VO2max, 75.1% ± 3.1% HRmax, and 5.8 ± 2.7 mmol·L-1, respectively. However, VO2 and HR were substantially higher for periods of the race as peak values were 83.5% ± 11.4% and 89.9% ± 1.7% of max, respectively. In conclusion, the present test is reliable and sensitive, thus providing a sailing-specific alternative to traditional physical testing of elite trapeze sailors. Additionally, on-water racing requires moderate aerobic energy production, although oxygen consumption can approach maximal levels for short periods of time.